Fundamental Studies on the Field Stripping System of Oil Palm Fruitlets - Suryanto, Hadi (1994)
In the present harvesting system, fresh fruit bunch (FFB) is transported and sterilized in the mill as a whole material instead of only fruitlets. This procedure causes some problems such as extra costs to transport and to sterilize the stalk, difficulty to heat the heavy bunch, and oil loss absorbed by the empty bunch. To overcome this problem, an attempt was made to separate the fresh-fruitlets from the cut spikelets in the field, so that only the fruitlets wil l be transported to the mill, while their stalks will be left in the field as mulch. The required steps of the proposed in-field stripping system are to reduce the removal force of fruittet, to prepare the cut spikelets as threshed material, and to detach loose fruitlets from the cut spikelets using a drum thresher. In order to accomplish the in-field stripping process, attempts were made: 1) to identify effective treatments which may accelerate the loosening process of fruitlets such that it can be stripped easily without deteriorating the oil quality, 2) to establish design parameters for cutting the spikelets from the treated bunch by means of a knife blade or a circular saw, 3) to develop an experimental drum thresher and to study the effects of various design constrains on the threshing performance. Bruise index, an indicator of the quality of stripped fruitlets due to the introduction of the thresher, was developed. Some physical properties of the oil palm fruitlets pertaining to the design of the thresher were also identified. The fruitlets abscission could be hastened by spray ing ethephon on cut spikelets or the brushing this chemical on the cut stalk of FFB. Its effect on the percentage of detached fruitlets and the removal force of the fruitlet were significant. This application did not affect the development of free fatty acid content. Low speed cutting tests using a knife blade showed that the specific cutting force and energy for the stalk and spikelet were significantly influenced by the knife edge angle, oblique angle, shear angle, but not by the cutting speed. Experiments using a circular saw showed that the total cutting power requirement for the bunch was directly proportional to the thickness of material, feeding rate, and the rotational speed of saw.